1989
DOI: 10.1002/zaac.19895770114
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 3‐dimethylamino‐(1,1 ‐dimethyl) propyl magnesium chloride with tin (IV) and tin (II) chlorides. Stabilization of a SnCl+ cation in the new tin cluster [Me2NCH2CH2C(Me2)SnCl]3 · SnCl2

Abstract: The reactions of the functional Grignard reagent Me2 NCH2CH2C(Me2)MgCl (4) with tin tetrachloride, dimethyltin dichloride, and tin (II) chloride are described. From the reactions the compounds bis(3‐dimethylamino‐1,1‐dimethylpropyl) tin dichloride, [Me2NCH2CH2C(Me2)]2SnCl2 (5), dimethyl(3‐dimethylamino‐1,1‐dimethylpropyl) chlorostannane, Me2ClSnC(Me2)CH2CH2NMe2 (6), 1,1,2,2‐tetramethyl‐1,2‐bis(3‐dimethylamino‐1,1‐dimethylpropyl) distannane,[Me2SnC(Me2)CH2CH2NMe2]2 (7), 3‐dimethylamino‐(1,1‐dimethyl)propyl tin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…4. There is no contact between tin atoms Sn1, Sn2, and Sn3, which enables us to compare 10 with previously published compounds cyclo-[(L CN 2 Sn) 2 -m-(SnL CN )-m-(OH)] [15], [Me 2 NCH 2 CH 2 C(Me) 2 SnCl] 3 .SnCl 2 [16] and a triply chelated Sn(IV)e Sn(II)eCl [17] complex which are the only proposed complexes of such type. The Sn4 atom is located 1.596 Å above the plane determined by Sn1, Sn2, and Sn3 atoms.…”
Section: Resultsmentioning
confidence: 99%
“…4. There is no contact between tin atoms Sn1, Sn2, and Sn3, which enables us to compare 10 with previously published compounds cyclo-[(L CN 2 Sn) 2 -m-(SnL CN )-m-(OH)] [15], [Me 2 NCH 2 CH 2 C(Me) 2 SnCl] 3 .SnCl 2 [16] and a triply chelated Sn(IV)e Sn(II)eCl [17] complex which are the only proposed complexes of such type. The Sn4 atom is located 1.596 Å above the plane determined by Sn1, Sn2, and Sn3 atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in 3, the central lead atom is significantly more shielded according to a smaller contribution to the paramagnetic contribution term. In addition, fast fluctuation of the lithium counterion in 2 or 3 can be attributed to a upfield shifting of the 7 Li NMR resonances to +0.68 ppm (2) and +1.08 ppm (3) in comparison to the parent lithium stannate 1 (δ = +2.12 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, homonuclear as well as heteronuclear molecules with E-E bonds become less stable when E represents tin and or lead. Moreover, within this class of compounds, discrete branched oligomers with more than one E-E bond are rare compared with their linear analogs [6][7][8][9][10]. It has been shown that reactions of lead(II) halides with Grignard reagents involved disproportionation processes leading to plumbates of type [MgBr(THF) 5 3 ] (Bp = 4-Biphenyl) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Especially the coordination mode about the tin atom and the strength of the intramolecular N→Sn coordination as a function of the identity of the substituents R and R′ were studied . With growing environmental awareness, nontoxic inorganic tin compounds lacking any tin–carbon bonds are in the focus of research . Amino alcoholate derivatives of tin are such inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%